Sympathetic Nerve-Mediated Fellow Eye Pain During Sequential Cataract Surgery by Regulating Granulocyte Colony Stimulating Factor CSF3 - Fan, Zheng; Fan, Caixia; Qi, Benxiang; Zhang, Bin; Li, Wenfeng; Qi, Xia; Liu, Xiaomin; Zhang, Bi Ning; Huang, Yusen (Frontiers in Cellular Neuroscience, 2022)
Patients were found to experience more pain during the second eye cataract surgery compared with their first eye surgery. This study aimed to explore the inflammatory alterations along time in the fellow eye after the first eye surgery and to reveal the underlying mechanism. Eighty patients with bilateral cataract were recruited and were divided into four groups based on the time of having the second eye surgery. The second eye aqueous humor samples were collected just before surgery and analyzed by mass spectrometry and PCR array. Cytokine activity was enriched in the aqueous humor of the contralateral eye with granulocyte colony-stimulating factor CSF3 significantly upregulated at both gene and protein levels. Rabbits with or without superior cervical ganglionectomy (SCGx) were subject to lensectomy to mimic human situation. In both human and rabbit models, the fellow eye CSF3 peaked at one week post the first eye surgery. Consistently, more neutrophils were recruited to the contralateral eye aqueous humor. Corneal sensitivity and trigeminal electrophysiology were recorded to imply the pain severity in rats receiving capsulorrhexis and with or without SCGx. More intense pulse in the contralateral trigeminal ganglion after the rat receiving one eye surgery. SCGx could effectively reduce the fellow corneal sensitivity and trigeminal nerve pain. These alterations were under direct regulation of the sympathetic nerves on the surgical eye side. Our results suggest CSF3 and sympathetic activity could serve as potential analgesic targets during ocular surgeries.